DUALISME MODEL PERLINDUNGAN SAKSI TINDAK PIDANA KORUPSI DI KOMISI PEMBERANTASAN KORUPSI - Sukiyawati; Alif Rahman (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
Witnesses to criminal acts of corruption handled by the Corruption Eradication Committee often experience threats or violence so they ask for help from the Corruption Eradication Commission, but it turns out that there are other institutions that have the authority to protect them, such as the LPSK, so the research will examine and analyze the dualism of the model for protecting witnesses to corruption crimes at the Corruption Eradication Commission. This research uses normative juridical, legislative research approaches, primary legal materials on the Witness and Victim Protection Law, the Corruption Eradication Commission Law. Secondary legal materials, journals, books and other references that have relevance to this research. The analysis technique used is descriptive analytical, the interpretation used is systematic and grammatical. The research results show that the Corruption Eradication Commission Law regulates that the authority to provide protection is the Corruption Eradication Committee (KPK) as regulated in Article 15, while in the Witness and Victim Protection Law it is the Witness and Victim Protection Agency (LPSK), so there is overlapping authority. So that each institution can provide protection. However, this problem can be resolved by using principles, namely the principle of lex specialis derogat legi generalis or specific laws overriding general laws. So in relation to witness protection, you can use the Witness and Victim Protection Law. In the future, suggestions need to be made to revise the Corruption Eradication Commission Law so that it removes the authority of the Corruption Eradication Commission (KPK) to provide witness protection and regulates the LPSK as an institution that is given the authority to protect witnesses. So that efforts to synchronize witness protection are realized that are good and correct.